2022
DOI: 10.3390/geriatrics7050105
|View full text |Cite
|
Sign up to set email alerts
|

Key Factors and AI-Based Risk Prediction of Malnutrition in Hospitalized Older Women

Abstract: The numerous consequences caused by malnutrition in hospitalized patients can worsen their quality of life. The aim of this study was to evaluate the prevalence of malnutrition on the elderly population, especially focusing on women, identify key factors and develop a malnutrition risk predictive model. The study group consisted of 493 older women admitted to the Asunción Klinika Hospital in the Basque Region (Spain). For this purpose, demographic, clinical, laboratory, and admission information was gathered. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This functionality provides health professionals and caregivers with a nutritional decision support system that considers not only the different nutritional needs (e.g., malnutrition risk, intake level, or the need for texture-adapted meals) but also the whole environment of an older patient, such as sociodemographic factors (e.g., sex, age…), psychosocial factors (e.g., psychosocial disorders), and morbidity factors (diseases). In addition, the personalized nutritional guidance [ 50 ] that offers this solution is divided into two types of recommendations, i) dietary and nutrition guidelines and ii) menu suggestions. In the first type, diet, fortification, food and liquid adaptation, supplementation, enteral nutrition, and follow-up areas are managed, whereas in the second type, different examples or suggestions of menu types and their ingredients are offered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This functionality provides health professionals and caregivers with a nutritional decision support system that considers not only the different nutritional needs (e.g., malnutrition risk, intake level, or the need for texture-adapted meals) but also the whole environment of an older patient, such as sociodemographic factors (e.g., sex, age…), psychosocial factors (e.g., psychosocial disorders), and morbidity factors (diseases). In addition, the personalized nutritional guidance [ 50 ] that offers this solution is divided into two types of recommendations, i) dietary and nutrition guidelines and ii) menu suggestions. In the first type, diet, fortification, food and liquid adaptation, supplementation, enteral nutrition, and follow-up areas are managed, whereas in the second type, different examples or suggestions of menu types and their ingredients are offered.…”
Section: Resultsmentioning
confidence: 99%
“…After identifying the key factors that contribute to malnutrition in older adults in a previous study carried out by our research group [ 50 ], those variables were used to develop an AI-based model for predicting the risk of malnutrition for this population. A total number of fifteen variables was introduced in the prediction system, and a three-optional response was obtained: low, medium, and high risk of malnutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Another study of hospitalized elderly females found that 63.9% were at risk of malnutrition or were experiencing malnutrition, proposing the negative influence of socioeconomic differences and increased depressive states. 28 Outside of disease, greater age in general exerts gradual yet dramatic effects on nutrition. Poor physical functionality hinders the ability for elderly individuals to maintain muscle mass, leading to progressive muscle catabolism, a common process in aging.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with other single-center studies that nd that females are associated with higher risks of malnutrition compared to males, although the mechanisms behind this observation are still poorly understood. [24][25][26] This discrepancy highlights the need for deeper investigation as to the source of gender miscalibration or consideration or retraining of gender-speci c malnutrition risk prediction models. Furthermore, in sensitivity analyses, we discovered that calibration intercepts were signi cantly different between patients on commercial insurance, Medicaid, or Medicare.…”
Section: Discussionmentioning
confidence: 99%